Move! : how the new science of body movement can set your mind free - Williams, Caroline, 1975- (Hanover Square Press, 2022)
A veteran science journalist explores the latest research on the relationship between brain health and physical activity and discusses how the simplest movements can reactivate our bodies and help relieve anxiety and depression and improve memory and creativity.